2023
DOI: 10.1038/s41531-023-00578-x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha synuclein modulates mitochondrial Ca2+ uptake from ER during cell stimulation and under stress conditions

Meraj Ramezani,
Alice Wagenknecht-Wiesner,
Tong Wang
et al.

Abstract: Alpha synuclein (a-syn) is an intrinsically disordered protein prevalent in neurons, and aggregated forms are associated with synucleinopathies including Parkinson’s disease (PD). Despite the biomedical importance and extensive studies, the physiological role of a-syn and its participation in etiology of PD remain uncertain. We showed previously in model RBL cells that a-syn colocalizes with mitochondrial membranes, depending on formation of N-terminal helices and increasing with mitochondrial stress1. We have… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 131 publications
0
5
0
Order By: Relevance
“…A comprehensive study led by Przedborski and Schon used several different techniques to demonstrate that wild-type monomeric αSyn is localized to ER–mitochondria contact sites at MAM domains and not within the mitochondria, as was previously thought [ 51 ]. Since then, several other studies from different groups have also demonstrated that αSyn can be found at MAM domains [ 52 , 53 , 54 , 55 ]. Yet, other studies have continued to associate αSyn within the mitochondria itself [ 56 , 57 , 58 ].…”
Section: Overview Of Alpha-synucleinmentioning
confidence: 99%
See 4 more Smart Citations
“…A comprehensive study led by Przedborski and Schon used several different techniques to demonstrate that wild-type monomeric αSyn is localized to ER–mitochondria contact sites at MAM domains and not within the mitochondria, as was previously thought [ 51 ]. Since then, several other studies from different groups have also demonstrated that αSyn can be found at MAM domains [ 52 , 53 , 54 , 55 ]. Yet, other studies have continued to associate αSyn within the mitochondria itself [ 56 , 57 , 58 ].…”
Section: Overview Of Alpha-synucleinmentioning
confidence: 99%
“…Lastly, since the ER is the primary site for intracellular Ca 2+ storage, Ca 2+ homeostasis at MAM domains is crucial in ER and mitochondrial communication, with the tight control of mitochondrial Ca 2+ import essential for cellular homeostasis. To investigate Ca 2+ homeostasis, independent measurements of Ca 2+ stores at the ER and Ca 2+ import into the mitochondria have been routinely performed, thereby indirectly assessing Ca 2+ homeostasis at MAMs [ 53 , 95 ]. Improved developments in genetically encoded calcium indicators (GECIs), such as fluorescence resonance energy transfer (FRET) and bioluminescence resonance energy transfer (BRET), have better enabled the steady-state assessment of Ca 2+ concentration [ 96 , 97 ].…”
Section: Mitochondria-associated Er Membranes (Mams)mentioning
confidence: 99%
See 3 more Smart Citations